Penggunaan Media Audio Visual dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fiqih - faizah, fina (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
Fiqh is often considered a difficult subject due to its theoretical and practical components, such as ablution, dry ablution, and prayer, which are hard to grasp through lectures alone. This study focuses on implementing audio-visual media in Fiqh learning for Grade IX students at SMP Islam Kepung to improve their learning outcomes. The goal is to describe the use of audio-visual tools as an interactive alternative in religious education. This qualitative descriptive research uses observation, interviews, and documentation for data collection. The findings show that audio-visual media enhances student engagement, clarifies abstract material, and improves understanding of worship practices. Supporting factors include technological facilities and teacher creativity, while barriers include limited time, lack of teacher training, and technical issues. Overall, audio-visual media proves effective in increasing student achievement when supported by proper planning and teacher competence.